Oil in Venezuela: Triggering Violence or Ensuring Stability? A Context-sensitive Analysis of the Ambivalent Impact of Resource Abundance - Annegret Mähler (German Institute of Global and Area Studies (GIGA), 2009)
This paper studies the causal factors that make the oil-state Venezuela, which is generally characterized by a low level of violence, an outlier among the oil countries as a whole. It applies a newly elaborated 'context approach' that systematically considers domestic and international contextual factors. To test the results of the systematic analysis, two periods with a moderate increase in internal violence in Venezuela are subsequently analyzed, in the second part of the paper, from a comparative-historical perspective. The findings demonstrate that oil, in interaction with fluctuating non-resource-specific contextual conditions, has had ambiguous effects: On the one hand, oil has explicitly served as a conflict-reducing and partly democracy-promoting factor, principally through large-scale socioeconomic redistribution, widespread clientelistic structures, and corruption. On the other hand, oil has triggered violence-primarily through socioeconomic causal mechanisms (central keywords: decline of oil abundance and resource management) and secondarily through the long-term degradation of political institutions. While clientelism and corruption initially had a stabilizing effect, in the long run they exacerbated the delegitimization of the traditional political elite. Another crucial finding is that the impact and relative importance of oil with respect to the increase in violence seems to vary significantly depending on the specific subtype of violence. – – Erdöl in Venezuela: Auslöser von Gewalt oder Stabilitätsfaktor? Eine kontextsensible Analyse der ambivalenten Auswirkungen von Ressourcenreichtum. Dieser Beitrag analysiert die Faktoren, die den Erdölexporteur Venezuela, der sich durch ein grundsätzlich niedriges Gewaltniveau auszeichnet, zu einem abweichenden Fall innerhalb der Debatte um die erhöhte Gewaltwahrscheinlichkeit in Erdölstaaten machen. Methodisch kommt ein neu erarbeiteter 'Kontextansatz' zur Anwendung, der den jeweiligen Einfluss innerstaatlicher und internationaler Kontextfaktoren systematisch überprüft. Um die Befunde der systematischen Analyse zu verifizieren und zu erweitern, werden im zweiten Teil des Papers in einer historisch-vergleichenden Analyse zudem zwei Phasen eines moderaten innerstaatlichen Gewaltanstiegs in Venezuela untersucht. Die Ergebnisse zeigen, dass Erdöl im jeweiligen Zusammenspiel mit unterschiedlichen nicht-ressourcenspezifischen Kontextfaktoren einen ambivalenten Einfluss ausüben kann: auf der einen Seite hat Erdöl in Venezuela - primär über breit angelegte staatliche Verteilungspolitiken, klientelistische Strukturen und Korruption - eindeutig als konfliktreduzierender und teils auch demokratiefördernder Faktor gewirkt. Auf der anderen Seite hat Erdöl aber auch niedrigschwellige Gewalt gefördert; dies vor allem über sozioökonomische Kausalmechanismen (Verfall der Erdölpreise und spezielles Ressourcenmanagement) und nachrangig über den langfristig verursachten Verfall politischer Institutionen. Während folglich Klientelismus und Korruption kurzfristig einen stabilisierenden Effekt hatten, haben sie langfristig zur Delegitimierung der politischen Elite geführt. Ein weiterer zentraler Befund ist, dass der konkrete Einfluss des Erdöls auf Gewalt je nach spezifischer Form der Gewalt deutlich zu variieren scheint.
Keywords: 300; Venezuela; natural resources; oil; political economy; violence; contextual sensitivity; Mineralölwirtschaft; Erdölpolitik; Gewalt; Verteilungspolitik; Patronage; Korruption; Venezuela